The evaluation of relationship mapping as a tool for understanding the experience of change - Neke, Justine Cayley (School of Management Studies, 2023)
The research for this dissertation was conducted at the Western Cape site of a national manufacturing organisation in the food and beverages industry. The study set out to attain two primary goals. The first was to examine the effectiveness of relationship mapping (a method for graphically depicting mental models) as a tool for exploring the participants' experience of, and evaluation of 'planned organisational change'. The second goal was to investigate the possible impact of relationship mapping on those using the method. Research results for both of these goals were examined through three 'lenses' or frames of analysis, 'empowerment', 'communication', and 'understanding the change'. These frames of analysis were derived from reviewed literature and interaction with the organisation. Incorporated into the design was an analysis of group processes, as an additional check on the impact of the relationship mapping procedure. The study assessed the above goals across four, hierarchically-divided organisational levels, with a total of 56 participants. A classical control group design was used, incorporating qualitative and quantitative methods. Control group participants underwent in-depth interviews, semi-structured focus group discussions and a group process scale (assessing group interaction). In addition to these, the experimental groups underwent relationship mapping, use of the group process scale, and a post relationship mapping questionnaire. Thematic and statistical analyses were used for the examination of qualitative and quantitative results, respectively. Although causality cannot be inferred with certainty, results indicate that these experimental groups paid increased attention to inter-relationships, questioning and problem solving, and the production of new information. Participants recognised that relationship mapping impacted on their sense of 'empowerment' by allowing for participation, facilitating thinking, and provoking personal realisations. Relationship mapping was seen as altering participant perception of communication and improving their understanding of the change.